Legal Construction of the ‘Municipal Filter’ for Developing Local Self-Government in Russia - SOLOVEV, Sergey Gennadevich; MAYOROV, Vladimir Ivanovich; PETROV, Andrey Yuryevich (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018DO - 10.14505//jarle.v9.5(35).32, 2018)
This article analyzes the potential of the legal structure supporting municipal candidates for the post of a governor of some federal subject of the Russian Federation (known as the ‘municipal filter’) for the development of the Russian local self-government. The authors consider the key theoretical and practical problems associated with substantive and procedural aspects of the existing support mechanism of candidates for the post of the highest official of a federal subject of the Russian Federation. The authors also propose a set of legal measures aimed at improving the legal structure under study.